Not separate but equal? The impact of multiple-defendant trials on juror decision-making - Wilford, Miko M. (Psychology, crime & law, 2018)
Suspects accused of involvement in the same crime can be tried in one multiple-defendant trial. While research has long demonstrated the difficulties of being a juror, no published work has examined whether multiple-defendant trials compound these difficulties. The current research recruited both student and community samples to determine whether trying multiple defendants would increase conviction rates for individual defendants. Every participant watched one of three trial videos - a single defendant against whom the State had a strong case (single-strong), a single-defendant against whom the State had a weak case (single-weak), or a multiple-defendant trial combining both defendants (multiple-defendant). The findings demonstrated an overshare effect - when the defendants were tried together, overall conviction rates for both defendants increased relative to when they were tried alone, though the pattern of results differed by study sample. Although we are unable to provide a definitive mechanism underlying the results, the best explanation seems to be that multiple-defendant trials prompt jurors to engage in a joint evaluation of the defendants, rather than single evaluations of each. Consequently, participant-jurors’ perceptions of each defendant are impacted by how they compare with one another. Thus, the current research casts some doubt on the fairness of multiple-defendant trials.